Ovidiu Papadima – de la „o viziune românească a lumii” la „creatorii şi lumea lor” - Iordan Datcu (Revista de Istorie și Teorie Literară)
In the first part of his life as a writer, he was mostly a literary critic.The main characteristic of his book A Romanian vision of the World is the orthodox perspective about the Romanian popular art. In the Romanian people beliefs, God is always present, his image being the Biblical one, but much more human. A special touch of the old peasants mentality was given by “the sentiment of love and intimity for the nature”, about he was believing that she is blessed to by God. Dorina Grasoiu has published the anthology The life of Ovidiu Papadima’s books (Vestala Publishing House, 2004).